MyDay - Alexandra Ívarsdóttir 1995-; Eiríkur Birkir Ragnarsson 1984-; Ragnar Ingi Ragnarsson 1987- (2017)
MyDay is a visual scheduling software designed for children that rely on visual scheduling in their daily life, as well as their teachers and parents. The idea for this project was developed in the class, User centred software development, at Reykjavík University. MyDay is divided into a web client and an app client. The web client is for the parents and teachers to create a home or school schedule for the children. There they can also keep a list of all the children they need and access their information. The app client is designed for the children and gives the child access to the home and school schedule that has been created for that particular child. With myDay the child can always have all his schedules easily accessible and therefore reduces stress and anxiety towards uncertainty in the child’s schedule which is very common with children on the autism spectrum as an example. MyDay aims to make the lives of every person that needs this kind of visual scheduling easier. It saves time for the parents and teacher that need to create these schedules on a regular basis and it reduces the use of plastic and paper since none is needed with myDay.